The Effect of The Socioeconomic Variety in Greater Cairo on Transport Mode Choices - Yanni, Rafik (AUC Knowledge Fountain, 2026)
In the last decade, Egypt has experienced a noticeable upgrade in its infrastructure investment, implementing a lot of transport projects, especially in the Greater Cairo region. In a city with over 20 million residents, variations lie in socioeconomic elements like income, age, gender, and neighborhood, which shape people’s choice of mobility modes based on their culture and lifestyle. The questions then become: whom are these new projects targeting? What are the barriers to using these services? And is there any willingness to change commuting habits if conditions changed? This thesis investigates how the socioeconomic variety in Greater Cairo metropolitan region influences the transport mode choices for individuals, using online surveys and semi-structured phone calls from 394 respondents across different neighborhoods. After categorizing respondents into 5 different social groups, the results showed that the primary motives for mode preferences were safety, comfort, and convenience, regardless of gender. Also, it showed that there was a tendency towards changing the commuting mode among four social groups: vulnerable, poor, lower, and upper-middle groups, with the change varying to private cars, better public transport mode, and ride-hailing applications. Though 60% of affluent people still preferred using private vehicles, some of them indicated a conditional shift towards an enhanced public transport service, and 40% indicated they would shift directly if a better alternative is present. Additionally, the thesis proposes a comprehensive model that enables transport leaders to consider multiple social and economic dimensions, thereby supporting their decision-making process. Lastly, the thesis offers both short-term and long-term solutions to enhance social cohesion in the transport sector.